Survey of T1 and T2 Energies of Intramolecular Singlet Fission Chromophores - Guoying Yao; Zhenyu Yang; Tao Zeng (Photochem, 2024)
Singlet fission is a desired process in photovoltaics since it enhances photoelectric conversion efficiency. Intramolecular singlet fission is of special interest as the fission efficiency can be improved through tuning configurations between chromophore units that are covalently connected. However, intramolecular singlet fission chromophores feature a large tetraradical character, and may tend to dissatisfy the <semantics>E<mfenced separators="" open="(" close=")">T2</mfenced>>2E<mfenced separators="" open="(" close=")">T1</mfenced></semantics> criterion for all singlet fission chromophores, intramolecular or not. We performed spin-flip time-dependent density functional theory calculations for a collection of representative intramolecular singlet fission chromophores to show that this is indeed the case.